2021
DOI: 10.1007/s40750-021-00176-2
|View full text |Cite
|
Sign up to set email alerts
|

Crowd Salience Heightens Tolerance to Healthy Facial Features

Abstract: Objective Recent findings suggest crowd salience heightens pathogen-avoidant motives, serving to reduce individuals’ infection risk through interpersonal contact. Such experiences may similarly facilitate the identification, and avoidance, of diseased conspecifics. The current experiment sought to replicate and extend previous crowding research. Methods In this experiment, we primed participants at two universities with either a crowding or control experience before hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 81 publications
1
2
0
Order By: Relevance
“…Our studies show that inclusion becomes more unpleasant when disease salience is high (vs. low), suggesting that social inclusion is less rewarding due to the salient costs of being included in social interactions. Consistent with our finding, recent research on crowd salience has shown that experimentally manipulated crowding primes lead to increased concerns of disease and shape interpersonal preferences toward those who appear healthy when given the choice (Brown et al, 2021; Brown & Sacco, 2022). Similarly, recent work on the quantity of social interactions (e.g., social contact frequency) showed that high levels (vs. moderate levels) of social interactions are associated with little health/well-being benefits and even higher mortality risks (Ren et al, 2022; Stavrova & Ren, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…Our studies show that inclusion becomes more unpleasant when disease salience is high (vs. low), suggesting that social inclusion is less rewarding due to the salient costs of being included in social interactions. Consistent with our finding, recent research on crowd salience has shown that experimentally manipulated crowding primes lead to increased concerns of disease and shape interpersonal preferences toward those who appear healthy when given the choice (Brown et al, 2021; Brown & Sacco, 2022). Similarly, recent work on the quantity of social interactions (e.g., social contact frequency) showed that high levels (vs. moderate levels) of social interactions are associated with little health/well-being benefits and even higher mortality risks (Ren et al, 2022; Stavrova & Ren, 2021).…”
Section: Discussionsupporting
confidence: 91%
“…If so, these findings are consistent with previous reports that adults' sick face perception is malleable and has ongoing flexibility. For example, priming adults about disease (e.g., through images of contagious symptoms) promotes sickness avoidance (Brown et al, 2021), suggesting a flexible threat‐management system that is calibrated to environmental input (i.e., cues of disease). In this study, we may have similarly primed children.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of disease transmission through interpersonal contact suggests this avoidance could mitigate disease transmission (Hoang et al, 2019 ; Jones et al, 2008 ). This aversion should be especially apparent when people have affiliative opportunities with others unlikely to transmit the disease (Brown et al, 2021a ). Both acute salience of disease and heightened levels of pathogen avoidance motives on a dispositional level foster aversive responses.…”
Section: Disease Avoidance and Social Perceptionsmentioning
confidence: 99%